Takhrij and Syarah Hadiths of Agrotechnology: The Importance of Farming - Rima Nur Maulida; Wahyudin Darmalaksana; Ida Yusidah (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a type of qualitative through library and field studyapproach. Takhrij and commentary tradition The results and discussion of this research are that it is important to do farming to meet the needs of human life. The conclusion of this research is the takhrij and syarah hadith of the Prophet SAW about the importance of farming, farming is important because it provides many benefits for human life on earth and has been recommended by the Prophet since long ago.